2018
DOI: 10.1007/978-3-319-75402-4_19
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and Reproducibility of In Vivo Cone Density Measurements in the Adult Zebrafish Retina

Abstract: Zebrafish (Danio rerio) are widely used as an experimental model for a wide range of retinal diseases. Previously, optical coherence tomography (OCT) was introduced for quantitative analysis of the zebrafish cone photoreceptor cell mosaic; however no data exists on the intersession reproducibility or intrasession repeatability of such measurements. We imaged 14 wild-type (WT) fish three times each, with 48 h between each time point. En face images of the UV cone mosaic were generated from the OCT volume scans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The combination of these decisions resulted in a relatively high mortality rate per imaging session (∼20% in pilot studies, ranging from 0%–75% mortality per imaging session). True longitudinal imaging has been demonstrated in wild-type fish, 28 , 29 so it should be possible to perform longitudinal imaging of degeneration if OCT scan time is reduced or alternate anesthetic protocols are used. This study examined ablation of a single photoreceptor subtype throughout the retina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of these decisions resulted in a relatively high mortality rate per imaging session (∼20% in pilot studies, ranging from 0%–75% mortality per imaging session). True longitudinal imaging has been demonstrated in wild-type fish, 28 , 29 so it should be possible to perform longitudinal imaging of degeneration if OCT scan time is reduced or alternate anesthetic protocols are used. This study examined ablation of a single photoreceptor subtype throughout the retina.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by Huckenpahler et al 29 and Toms et al 28 have demonstrated longitudinal imaging of the wild-type zebrafish UV cone mosaic, phylogenetically corresponding to blue cones in humans and S-cones in mice. Imaging individual cones opens up the possibility of using OCT to monitor cone degeneration in disease models.…”
Section: Introductionmentioning
confidence: 99%
“…We do not think we can obtain reliable photoreceptor densities from our data, as our EM samples do not cover a large enough area, but we can compare the photoreceptor densities from Mäthger and colleagues to average photoreceptor densities reported by others in commonly used species. Rough approximations of photoreceptor densities in zebrafish, mouse, salamander, and Xenopus from the literature are as follows: (1) zebrafish ∼6.0 × 10 4 and ∼2.1 × 10 4 cells/mm 2 for rods and cones, respectively ( Huckenpahler et al, 2018 ; Van houcke et al, 2019 ); (2) mouse ∼3.3 × 10 5 to 5.1 × 10 5 and ∼8.7 × 10 4 to 1.6 × 10 5 cells/mm 2 for rods and cones, respectively ( Jeon et al, 1998 ); (3) salamander ∼4.4 × 10 3 and ∼3.5 × 10 3 cells/mm 2 for rods and cones, respectively ( Zhang and Wu, 2009 ); (4) Xenopus ∼7.3 × 10 3 and ∼6.4 × 10 3 cells/mm 2 for rods and cones, respectively ( Gábriel and Wilhelm, 2001 ). Note, this is only an approximation from the literature and is taken across retinal eccentricities and cone spectral sensitivities, where described.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the small size and optical properties of the zebrafish eye, en face images of the photoreceptor matrix can be produced at a single-cell resolution that is not possible with rodent and human eyes [ 125 , 126 ]. Quantification and tracking of individual cones is highly reproducible using this approach [ 127 ]. Voroni domain analysis has also been used to determine the cone-domain packing regularity and how this gradually decreases as the zebrafish aged from 3 to 12 months old [ 128 ].…”
Section: Robust Endpoints For Retinal Neuroprotection Studies In Zmentioning
confidence: 99%